Coupled modeling of Excavation Damaged Zone in Boom clay: Strain localization in rock and distribution of contact pressure on the gallery's lining. (September 2015) - Salehnia, F.; Collin, F.; Li, X.L.; Dizier, A.; Sillen, X.; Charlier, R.
Abstract: Around galleries excavated at depth in geological media, the creation of a damaged zone with significant irreversible deformation is generally unavoidable. In the case of a geological disposal system for high-level radioactive waste, the resulting change in the host rock properties in this damaged zone may potentially be important with respect to the long-term evolution and the performance of that system. In this context, predicting the extent of the so-called Excavation Damaged Zone (EDZ) and, possibly, the fractures' network topology remains a challenge. This study is aimed to simulate numerically the extension of this zone at the large scale's excavation, around the Connecting gallery (HADES URL, Mol, Belgium), in Boom clay host rock through analyzing the evolution of strain localization in shear bands mode. To realistically model the involved phenomena, the concrete lining is considered on the gallery wall highlighting its impacts on the evolution of convergence and EDZ around the gallery. The focus of the current paper is made on analyzing the coupled hydro-mechanical behavior of Boom clay host rock during and after the gallery excavation with respect to the evolution of localized shear bands around the gallery. This study is accompanied by the analysis of the contact mechanism on the interface between the clay massive and the lining. The obtained results reveal some interesting features regarding the contact phenomenon relatively to the evolution pattern of shear bands within the clay around the gallery. To assess the reliability of the proposed approach, a discussion on some in-situ observations during the gallery's construction is also performed based on which a good agreement is found between the in-situ evidence and simulated results.